Evaluating the Hatchery Program of a Highly Exploited Shrimp Stock (Fenneropenaeus chinensis) in a Temperate Marine Ecosystem - Xing, Lei; Chen, Yong; Tanaka, Kisei R.; Barrier, Nicolas; Ren, Yiping (Frontiers in Marine Science, 2022)
Hatchery programs are commonly used to enhance fishery stocks, while the efforts to minimize potential negative ecological impacts have grown in recent years. In China, Fenneropenaeus chinensis is a fast-growing, short-lived shrimp species with a high commercial value. F. chinensis fishery is heavily dependent on the hatchery program. We evaluated the trade-off between economic profits and ecological impacts of F. chinensis hatchery program in the Jiaozhou Bay of China. The total length of released individuals was 1.4 cm. The results showed that artificially released F. chinensis individuals experienced high predation pressure during the first two weeks. The economic profit peaked when 198 million individuals were released. The modeled hatchery program yielded a lower proportion of individuals with the increasing amount of F. chinensis release. The temporally uniform hatchery release was more efficient than other hatchery release scenarios (e.g., increasing the released amount year by year) in a long-term hatchery program. F. chinensis had the negative impacts on two large predatory fishes. Large fishes recovered at a slower rate than small fishes after the F. chinensis release stopped. Reducing fishing pressure could offset negative impacts of F. chinensis release on large fishes. The study indicates that the effectiveness of F. chinensis release cannot be enhanced by simply increasing the released amount. A long-term F. chinensis hatchery program with a large released amount may present additional challenges for managing natural resources in an ecosystem context.